Night‐time eating and body weight status among US adults, 2007–2016. Issue 6 (29th May 2019) - An, R.; Shi, Y.; Clarke, C.; Zhang, S.
Abstract: Background: The present study assessed the relationship between night‐time eating and body weight status among US adults, using in‐person 24‐h dietary recall data from a nationally representative survey. Methods: Individual‐level data ( n  = 23 003) came from the 2007–2016 National Health and Nutrition Examination Survey (NHANES) (five waves). Multivariate linear and logistic regressions were performed to estimate the effect of energy, sugar, fat and saturated fat intake during night‐time on body mass index (BMI), obesity (BMI ≥30 kg m –2 ), waist circumference (WC) and abdominal obesity (WC ≥88 cm in women; WC ≥102 cm in men), adjusting for daily total energy intake, physical activity, sleeping and other individual characteristics. Results: Approximately 36.5% and 56.7% of the NHANES adult participants had obesity and abdominal obesity, respectively. The proportion of energy, total fat, saturated fat and total sugar intake within the time window of 00.00 h to 05.59 h and 22.00 h to 23.59 h averaged 5.7%, 5.3%, 5.7% and 6.8%, respectively. Energy intake within the time window was not found to be associated with BMI, WC, obesity or abdominal obesity in the regression analyses. Sensitivity analyses applying alternative time windows to capture night‐time eating found night‐time intakes of energy, total fat, saturated fat and total sugar not to be associated BMI, WC, obesity or abdominal obesity. Conclusions: Night‐time eating was not found to be associated with body weight status in a US nationally representative adult sample. Restricting night‐time food consumption alone without an overall reduction in daily caloric intake may not prevent obesity. The findings of the present study warrant replication in a future experimental study with habitual dietary behaviour measures.